"I Knew You Were Trouble": Considering Childism(s), Shame Resilience, and Adult Caretaker Characters Surrounding YA Rape Survivor Protagonists. Issue 2 (3rd July 2018) - Moore, Amber
ABSTRACT: Adult characters in young adult (YA) literature remain largely unexamined. In this article, All the Rage (2015), Exit, Pursued by a Bear (2016), Speak (1999), and "Wolf" from The Rose and the Beast (2000) are closely analyzed to evaluate whether these characters engaged in childism(s). Particularly, YA sexual assault narratives warrant critical consideration, as caretaker characters hold potential to significantly impact assaulted adolescents' abilities to enact shame resilience. The four stories suggest that how parent and school-based professional characters impact survivor protagonists is directly correlated with if, or the degree to which, the grown ups participated in "positive" or "negative" childism.